The Nature and Degree of NGO Interaction with the United Nations within the ECOSOC : Consultative Status Program - Mowell, B.D. (Estudios Internacionales, 2025)
The main vehicle in the UN-NGO dynamic is the consultative status program within the UN Economic and Social Council (ECOSOC). Existing literature addresses the UN with regard to facilitating formal collaboration with international civil society, but little research has been undertaken to examine macro-scale patterns of NGOs within such collaborations. This study sought to partly address the latter gap in the literature by examining the nature and degree of NGO participation within the UN-ECOSOC consultative status program. The results of a survey sent to a random sample of 10 percent of NGOs holding consultative status revealed that most organizations have minimal participation and a large minority of NGOs awarded the status do not appear to be actively engaged.